I Don't Understand What They Speak: Photovoice of Indonesian Higher Education Students - Sari, Tri Susmita; Naimah, Malikhatun; Martalina, Ardiana Wafda; Arjiani, Lisa Iin (Journal of English Teaching and Learning Issues, 2021)
This study discusses the problems and causes experienced by higher education students when listening to everything spoken by native speakers. They find it very difficult to understand speech spoken directly or from audio learning English. This makes them feel restless and uncomfortable in listening lessons and exams on campus while these subjects are very important for them as students. This study uses the photovoice methods in examining the problems experienced by several higher education students, so that it will focus more on the factors causing the problems and the problems experienced. The study was based on the experience of an English major in education. It involved four English speaking students and audio speakers. The study suggests that a parable occurred when an English education student understood the words of native speakers and audio speakers. It provides input to everyone associated with the study of English to recognize problems in understanding native speakers.